Assumptions of Grand Logics - Feibleman, J.K. author. aut Link
XIII, 283 p.
Keywords: A system of philosophy of the sort presented in this and the following volumes begins with logic. Philosophy properly speaking is characterized by the kind oflogic it employs, for what it employs it assumes, however silently; and what it assumes it presupposes. The logic stands behind the ontology and is, so to speak, metaphysically prior. One word of caution. The philosophical aspects of logic have lagged behind the mathematical aspects in point of view of interest and develop ment. The work of N. Rescher and others have gone a long way to correct this. However, their work on philosophical logic has been more concerned with the logical than with the philosophical aspects. I have in mind another approach, one that would call attention to the ontological (systematic meta physics) or metaphysical (critical ontology) aspects, whichever term you prefer. It is this approach which I have pursued in the following chapters. Since together they stand at the head of a system of philosophy which has been developed in some seventeen books, a system which ranges over all of the topics of philosophy, the chosen approach can be seen as the necessary one. But I have not written any logic, I have merely indicated the sort of logic that has to be written.